Review paper Plasmodium knowlesi in humans: a review on the role of its vectors in Malaysia - Vythilingam, I. (2010)
Plasmodium knowlesi in humans is life threatening, is on the increase and has been reported from most states in Malaysia. Anopheles latens and Anopheles cracens have been incriminated as vectors. Malaria is now a zoonoses and is occurring in malaria free areas of Malaysia. It is also a threat to eco-tourism. The importance of the vectors and possible control measures is reviewed here.